Pineal Gland Metastasis From Poorly Differentiated Carcinoma of Unknown Primary Origin - Cuoco, Joshua A.; Kortz, Michael W.; Benko, Michael J.; Jarrett, Robert W.; Rogers, Cara M.; Witcher, Mark R.; Marvin, Eric A. (Frontiers in Endocrinology, 2020)
Pineal metastasis is an exceedingly rare finding in patients with systemic malignancies. Such lesions are typically the manifestation of a primary lung cancer; nonetheless, a variety of malignancies have been reported to disseminate to the pineal gland including gastrointestinal, endocrine and skin cancers, among others. However, to our knowledge, pineal gland metastasis without a primary origin has yet to been described. Carcinoma of unknown primary origin is a heterogeneous group of cancers characterized by the presence of metastatic disease without an identifiable primary tumor on metastatic workup. Here, we present a case of a 65-year-old male found to have a heterogeneously enhancing lesion of the pineal gland as well as an enhancing lesion of the left cerebellar hemisphere. Comprehensive metastatic workup demonstrated multifocal metastatic adenopathy without an identifiable primary lesion. Stereotactic biopsy of the pineal lesion revealed poorly differentiated carcinoma with an immunophenotype most consistent with gastrointestinal origin. To our knowledge, this is the first case to describe a pineal gland metastasis without a primary origin. We discuss the relevant literature on pineal gland metastases as well as carcinoma of unknown primary origin.